Thyroid Function and the Risk of Alzheimer's Disease: A Mendelian Randomization Study - Marouli, Eirini; Yusuf, Lina; Kjaergaard, Alisa D; Omar, Rafat; Kuś, Aleksander; Babajide, Oladapo; Sterenborg, Rosalie; Åsvold, Bjørn O; Burgess, Stephen; Ellervik, Christina; Teumer, Alexander; Medici, Marco; et al. (Thyroid (New York, N.Y.), 2021)
Observational studies suggest an association between thyroid function and risk of dementia, but the causality and direction of these effects are unclear. We aim to test whether genetically predicted variation within the normal range of thyroid function and hypothyroidism is causally associated with the risk of Alzheimer's disease (AD). Mendelian randomization (MR) analyses using genetic instruments are associated with normal range thyrotropin (TSH) and free thyroxine (fT4) levels. Secondary analyses included investigation of the role of hypothyroidism. Bidirectional MR was conducted to address the presence of a potential reverse causal association. Summary statistics were obtained from the ThyroidOmics Consortium involving up to 119,715 individuals and the latest AD genome-wide association study data including up to 71,880 cases. MR analyses show an association between increased genetically predicted normal range TSH levels and a decreased risk of AD ( = 0.02). One standard deviation increased normal range TSH levels were associated with a decreased risk of AD in individuals younger than 50 years old ( = 0.04). There was no evidence for a causal association between fT4 ( = 0.54) and AD. We did not identify any effect of the genetically predicted full range TSH levels ( = 0.06) or hypothyroidism ( = 0.23) with AD. Bidirectional MR did not show any effect of genetic predisposition to AD on TSH or fT4 levels. This MR study shows that increased levels of genetically predicted TSH within the normal range and in younger individuals are associated with a decreased risk of AD. We observed a marginal association between genetically predicted full range TSH and AD risk. There was no evidence for an effect between genetically predicted fT4 or hypothyroidism on AD. Future studies should clarify the underlying pathophysiological mechanisms.